Neighbourhood walkability and the incidence of diabetes: an inverse probability of treatment weighting analysis - Booth, Gillian L; Creatore, Maria I; Luo, Jin; Fazli, Ghazal S; Johns, Ashley; Rosella, Laura C; Glazier, Richard H; Moineddin, Rahim; Gozdyra, Peter; Austin, Peter C (Journal of epidemiology and community health (1979), 2019)
People living in highly walkable neighbourhoods tend to be more physically active and less likely to be obese. Whether walkable urban design reduces the future risk of diabetes is less clear. We used inverse probability of treatment weighting to compare 10-year diabetes incidence between residents living in high-walkability and low-walkability neighbourhoods within five urban regions in Ontario, Canada. Adults (aged 30-85 years) who were diabetes-free on 1 April 2002 were identified from administrative health databases and followed until 31 March 2012 (n=958 567). Within each region, weights reflecting the propensity to live in each neighbourhood type were created based on sociodemographic characteristics, comorbidities and healthcare utilisation and incorporated into region-specific Cox proportional hazards models. Low-walkability areas were more affluent and had more South Asian residents (6.4%vs3.6%, p<0.001) but fewer residents from other minority groups (16.6%vs21.7%, p<0.001). Baseline characteristics were well balanced between low-walkability and high-walkability neighbourhoods after applying individual weights (standardised differences all <0.1). In each region, high walkability was associated with lower diabetes incidence among adults aged <65 years (overall weighted incidence: 8.2vs9.2 per 1000; HR 0.85, 95% CI 0.78 to 0.93), but not among adults aged ≥65 years (weighted incidence: 20.7vs19.5 per 1000; HR 1.01, 95% CI 0.91 to 1.12). Findings were consistent regardless of income and immigration status. Younger adults living in high-walkability neighbourhoods had a lower 10-year incidence of diabetes than similarly aged adults living in low-walkability neighbourhoods. Urban designs that support walking may have important benefits for diabetes prevention.